Ujung Kulon National Park Ecotourism as a Form of Public Conservation and Education Strategy for Endangered Animals: Literature Review - Fauziah, Firza; Istiqomah, Risci Afif; Saputri, Dina Anggun; Wakhidah, Anisatu Z. (Jurnal Biologi Tropis, 2024)
The oldest national park in Indonesia is Ujung Kulon National Park and is the last habitat of Javan Rhinoceros and other endangered animals. Habitat degradation and overexploitation are the main factors in the extinction of endangered animals. The condition is getting worst because the lack of public awareness about the importance of conserving endangered animals and their habitats. The method for conducting this research was based on the literature study. The results of this research indicate that strategic conservation actions will be implemented through conservation management practices such as: (1) development of JRSCA for the Javan rhinoceros, (2) effectiveness of TNUK management, (3) intensification of protection and patrols, (4) law enforcement, (5) education and involvement of local communities, (6) development of ecotourism, (7) development of Mount Honje as a habitat for the Javan rhino, (8) rhino research program including population surveys, biological and ecological research, (9) translocation and release of the Javan Rhino to develop the Javan Rhino population which is decrease. Educational programs that can be carried out are: (1) Art books, (2) Educational Games Based on Android, (3) Illustrated books, (4) Merchandise, (5) TNUK endangered animal conservation campaigns.